Competitive Sustainability: A Historical Materialist Analysis of Ideas, Institutions and Power Relations in the European Green Transformation - Porak, Laura (Momentum Quarterly, 2023)
With the European Green Deal (2019), the green transformation and thus ’competitive sustainability’ becomes the focus of the European Union’s political-economic strategy. During this, previously established beliefs about the connection between competitiveness and prosperity as well as existing European and global economic structures are being questioned. To enforce particular interests, the power struggles between member states, capital fractions and the EU are consequently focusing on the transformation process. In the context of the green transformation, this article sets out to analyze, firstly, discursive and institutional shifts in relation to competitiveness and, secondly, shifts in power relations in the EU. The analysis comes to two main conclusions: First, at the level of ideas about competitiveness and the institutions in this context, there are continuities with previous European political economic strategies. Second, the transformation process is shaped by a complex interplay of ideas about competitive sustainability and vested interests that ensure selective translation of ideas into EU political-economic strategy.